Design guideline for dyslexic children in reading application: a systematic literature review - Mohamed Masrop, Noor Azli; Zainuddin, Ghazali; Md Yunus, Asrina Suriani; Syed Sahuri, Sarifah Nurhanum; Sahrir, Muhammad Sabri (Penerbit KUIS, 2022)
Book chapter no 14 published by KUIS 2022